Calculation of inrush current using adopted parameters of the hysteresis loop. Issue 5 (19th August 2014) - Naghizadeh, Ramezan Ali; Vahidi, Behrooz; Hosseinian, Seyed Hossein; Sykulski, Jan
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose The primary purpose of this paper is to propose an accurate model for simulation of inrush current in power transformers with taking into account the magnetic core structure and hysteresis phenomenon. Determination of the required model parameters and generalization of the obtained parameters to be used in different conditions with acceptable accuracy is the secondary purpose of this work. Design/methodology/approach The duality transformation is used to construct the transformer model based on its topology. The inverse Jiles-Atherton (JA) hysteresis model is used to represent the magnetic core behavior. Measured inrush waveforms of a laboratory test power transformer are used to calculate a fitness function which is defined by comparing the measured and simulated currents. This fitness function is minimized by particle swarm optimization (PSO) algorithm which calculates the optimal model parameters. Findings An analytical and simple approach is proposed to generalize the obtained parameters from one inrush current measurement for simulation of this phenomenon in different situations. The measurement results verify the accuracy of the proposed method. The developed model with the determined parameters can be used for accurate simulation of inrush current transient in power transformers. Originality/value A general and flexible topology based model is developed in PSCAD/EMTDC software to represent the transformer behavior in inrush situation. The hysteresis model parameters which are obtained from one inrush current waveform are generalized using the structure parameters, switching angle, and residual flux for accurate simulation of this phenomenon in different conditions.